Analisis Komparatif Representasi Aspek Psikologis Dan Sosial Dalam Novel Ronggeng Dukuh Paruk Dan Bumi Manusia: Implikasi Pada Pembelajaran Sastra Di Sekolah Menengah Atas - Eny Junyanti (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
The research focuses on conducting a comparative study of social representation in two famous Indonesian novels, namely, "Ronggeng Dukuh Paruk" written by Ahmad Tohari and "Bumi Manusia" by Pramoedya Ananta Toer. The research explores the implications of the novel for Indonesian language teaching materials in secondary schools, which were revised by the Ministry of Education and Culture in 2018. These literary works, the abundance of value contained in social, cultural, and historical significance, are regarded as valuable assets that can enhance literary teaching with the aim of growing students' understanding of various aspects of Indonesian society. Qualitative methodology was used in this study to investigate how the integration of these two novels into the Indonesian language curriculum could enhance students' understanding of principles such as justice, identity, and social interaction. The study revealed that the inclusion of these novels in literary education not only expanded students' awareness of social and cultural issues but also increased their capacity for critical analysis and empathy. It is recommended that educators adopt an interdisciplinary approach when teaching literature, linking texts to broader social, historical, and cultural frameworks to facilitate students in developing a deeper understanding of their community and its underlying principles. The results of this research are expected to offer a new perspective on improving the curriculum of literature and pedagogical strategies in Indonesia, in particular in cultivating the social and critical awareness of students through literary studies.